3x+2y=9 2x+3y=11
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 22:02:19
3x+2y=92x+3y=113x+2y=92x+3y=113x+2y=92x+3y=113x+2y=9①2x+3y=11②①x2-②x3得:-5y=-15,y=3把y=3代入①得:3x+6=9,x=
3x+2y=9 2x+3y=11
3x+2y=9 2x+3y=11
3x+2y=9 2x+3y=11
3x+2y=9① 2x+3y=11②
①x2-②x3得:-5y=-15,y=3
把y=3代入①得:3x+6=9,x=1
所以原方程组的解是x=1,y=3
3x+2y=9 为一式 2x+3y=11 为二式
一式x2 【得三式】 二式x3 【得四式】
三式-四式 得 -5y=-15 y=3
带入一式 的3x+6=9
x=1
3x+2y=9 (1式) 2x+3y=11(2式)
将1式x2,得:6x+4y=18(3式)
将2式x3,得:6x+9y=33(4式)
将4式-3式,得:5y=15
解得y=3
将y=3代入1式,得:3x=3
解得x=1
y=3
3(x+y)-2(x-y)=11 4(x+y)+3(x-y)=9
4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11
根据3(x+y)-2(x-y)=11,4(x+y)+3(x-y)=9可得出x+y= ,x-y=
3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=
(x+y)(x-y)+(x-y)平方-(x-y)(3x-y) 其中x=-2 y=3分之一
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)
(x+y)(2x-3y)=?
3(x+y)-2(x-y)=11 4(x+y)+3(x-y)=9
接二元一次4(x+y)-3(x-y)=9;5(x-y)+2(x+y)=11
【2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2】/2(x-y)^2=
已知x-y=3,求[(x+y)(x-y)-(x-y)^2+2y(x-y)]除以的值
已知3x =2y 求x/x+y+y/x-y-y²/x²-y²
(x+y)(x+2y)(x+3y)(x+4y)=-40y的值为根号11
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
若2/x-1/y=3,求[y/x-y/x-y(x-y/x-x+y)]/x-2y/x的值
9y=3x-(x-1),4(x+y)-(2x+4)=8y
5x=3y,(2x+y)的平方=5x(x+y)+9